Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Please show your work!

3(5x - 6) = 6(2x - 12)


Sagot :

Answer:

x = -18

Step-by-step explanation:

Distribute: 3*5x = 15x ; 3*-6 = -18 ; 6*2x = 12x ; 6*-12 = -72

15x - 18 = 12x - 72

Add 18 to both sides: 15x = 12x - 54

Subtract 12x from both sides: 3x = -54

Divide both sides by 3: x = -18

Answer:

x= 17.666666...

Step-by-step explanation:

3(5x - 6) = 6(2x - 12)

(3 times 5x , 3 times  -6)             (6 times 2x, 6 times - 12)

15x-18 = 12x -72           (multiply insides)

-12x       -12x              (remove 12x from right side)

3x-19 = -72                (product)

   +19 = +19                (add 19 left side to remove it)

3x = 53                        (product)

x = [tex]\frac{53}{3}[/tex]                              (divide)

x= 17.666666...                (answer)

x = 17.67                     (if simplify)